Duration of fever and other symptoms after the inhalation of laninamivir octanoate hydrate for influenza treatment; comparison among the four Japanese influenza seasons from 2011–2012 to 2014–2015. Issue 9 (September 2016) - Ikematsu, Hideyuki; Kawai, Naoki; Iwaki, Norio; Kashiwagi, Seizaburo
Abstract: The duration of fever and other symptoms as markers of the clinical effectiveness of laninamivir octanoate hydrate (laninamivir) were investigated in the Japanese 2014–2015 influenza season and the results were compared with those of the previous three seasons, 2011–2012 to 2013–2014. From these four seasons, the data of 636 influenza A(H3N2) and 128 influenza B patients was available for analysis. No significant difference was found in their baseline characteristics. The median duration of fever for all A(H3N2) patients ranged from 32.0 to 41.0 h. The duration of fever in the 2014–2015 season was significantly shorter than that in the 2012–2013 and 2013–2014 seasons (p = 0.0204 and 0.0391, respectively), but the differences were within nine hours. The median duration of symptoms for A(H3N2) ranged from 80.0 to 89.0 h, with no significant difference among the four seasons (p = 0.2222). The median duration of fever for B patients ranged from 43.0 to 50.0 h, with no significant difference among the four seasons. The duration of the symptoms for B varied by season, but no significant difference was found among the four seasons. Over the four seasons, 44 adverse events were reported from among 921 patients, with all resolving without treatment. These results indicate the continuing effectiveness of laninamivir against influenza A(H3N2) and B, with no safety issues. It is unlikely that the clinical use of laninamivir has caused viral resistance in the currently epidemic viruses.